Analysis of Information System Success in the Colleges in East Java with Wijayanto’s Approach of Information System Success Model - Heri Wijayanto (Universitas Muhammadiyah Ponorogo, 2020)
The era of globalization, which is marked by reforms in the field of information, requires good top management support and can support the application of information systems for the creation of quality, useful, and competitive information. Information systems in colleges are tools for managers to complete both new roles and traditional roles, enabling managers to monitor, plan, and predict more precisely and quickly to respond quickly to changes in the business environment. The purpose of this study is to analyze the role of top management support as a moderating variable effect of product quality on use and analyze the role of organizational culture as a moderating variable the effect of the use on benefits. The population of this study was colleges in East Java, a sample of 164 colleges consisting of 57 colleges ranked in Webometrics, and 107 colleges ranked in Webometrics. The analysis came with the SEM-Amos 22 program. The results showed that top management support moderated the effect of product quality on pure use of moderation, and organization culture moderated the effect of the use on benefits in a quasi-moderation manner.